Testing physiologically-based resource allocation rules in laboratory experiments with Daphnia magna Straus - Nogueira, António (2012)
The rules governing the allocation of available resources to varying physiological processes are evaluated in three physiologically-based models of individual Daphnia. In laboratory experiments using a single clone, subjected to varying regimes of food deprivation, growth was found to vary inversely with food level, ceasing in the absence of food, implying that growth allocation is derived directly from food. Reproductive investment was reduced under food deprivation, ceasing at low food levels. By exposing juvenile and adult daphnia to varying food deprivation regimens during different periods within their intermoult interval, it was shown that instar durations vary as a function of body size and food availability independent of the age of the animal. For the first time, the role of variable instar duration, which critically influences physiological processes such as growth, moulting and reproduction in adult females, that has been neglected by existing Daphnia models, is explicitly incorporated in a physiological allocation model. The consequent model provides a simplified framework for modelling the consequences of food deprivation in cladocerans which has important application in population modelling and environmental risk assessment.